Ageing with a silver‐spoon: A meta‐analysis of the effect of developmental environment on senescence. Issue 5 (16th August 2018) - Cooper, Eve B.; Kruuk, Loeske E. B.
Abstract: What determines variation between individuals in how they senesce, and are environmental conditions experienced during development relevant to late‐life performance? We report a meta‐analysis of studies of wild populations to determine how the quality of the environment experienced during development affects rates of survival and reproductive senescence. From studies of 14 bird or mammal species, we calculated effect sizes for the interaction between the effects of environmental quality during development and age in predicting survival ( N = 18) or reproduction ( N = 30) over time in late life. We found no evidence that developmental environment affected rates of survival senescence (βmean = –1.2 × 10 −4 ± 0.022SE). However, a better developmental environment was associated with slower rates of reproductive senescence in late life (βmean = 0.062 ± 0.023SE), indicating a small, but significant, "silver‐spoon" effect of early‐life conditions that persisted through to late life. Our results illustrate how the effects of environmental conditions during development can persist throughout life, and indicate one possible cause of phenotypic plasticity in senescence.